Combined semiquantitative nail-enthesis complex ultrasonography and capillaroscopy in psoriasis and psoriatic arthritis - Cafaro, Giacomo; Bursi, Roberto; Valentini, Valentina; Hansel, Katharina; Perricone, Carlo; Venerito, Vincenzo; Bistoni, Onelia; Sebastiano, Manuela; Topini, Fabiana; Stingeni, Luca; Gerli, Roberto; Bartoloni, Elena (Frontiers in Immunology, 2025)
This pilot study investigates distinctive features within the nail-enthesis complex among Psoriatic arthritis (PsA), Psoriasis (PSO), Rheumatoid Arthrit is (RA), and Healthy Control (HC) groups, utilizing a combined approach of ultrasound (US) and nailfold videocapillaroscopy (NVC). Clinical assessments and comprehensive US and NVC evaluations of the nail-enthesis complex were conducted on 72 subjects (18 PsA, 16 PSO, 19 RA, 19 HC). Unsupervised clustering models and factor analysis were employed to identify patterns and interrelationships between US and NVC parameters. Significant structural differences were detected, emphasizing the discriminatory power of semiquantitative US scores (GS BUNES, Wortsman type). Trends in vascularization aligned with literature, showcasing dysregulated angiogenesis in PsA and PSO. The clustering model effectively distinguished HC from PsA subjects, revealing a potential continuum between PSO and PsA. RA subjects exhibited subsets with features akin to both HC and PsA/PSO, underscoring the complexity of its manifestations. This study provides insights into nail-enthesis complex alterations, highlighting distinctions among PsA, PSO, RA, and HC subjects. The clustering model emphasizes potential overlap between PSO and PsA. Factor analysis elucidates collinearity in US-detected characteristics, while suggesting limited discriminative power of some quantitative parameters. These findings advocate for further exploration in prospective trials, potentially predicting the evolution of undifferentiated early arthritis and arthritis onset in PSO patients.